RETRACTED: Visualization as a method of overcoming anxiety and nervous tension, reducing symptoms of depression and stress in difficult life situation - Makarova Elena; Degtyareva Elena; Kholina Oksana (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 84, 00001 (2024), https://doi.org/10.1051/bioconf/20248400001